Geschlecht, Bildung, Profession Ungleichheiten im pädagogischen Berufsfeld - Burren, Susanne; Larcher-Klee, Sabina (Studien zu Differenz, Bildung und Kultur, 2022)
Gender inequalities in society are also reflected in the professional field of education. The anthology deals with existing and new problems in pedagogical professions from the perspectives of professional history, educational policy and occupational sociology. The interrelationship between occupational history and gender relations is revealed, which renders insights for the development of the profession visible.